Formulation and Characterization of Glibenclamide Solid Lipid Submicroparticles Formated by Virgin Coconut Oil and Solid Matrix Surfactant - Mardiyanto Mardiyanto; Najma Annuria Fithri; Annisa Amriani; Herlina Herlina; Dwi Purnama Sari (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Glibenclamide has the biopharmaceutics classification system (BCS) class II which has high permeability and low solubility. The solubility of glibenclamide can be enhanced by forming solid lipid nanoparticles (SLN). This research has the aim to prepare and characterize SLN loading glibenclamide. The glibenclamide SLN formula was composed by using the liquid lipid as virgin coconut oil (VCO), PEG 6000 as a solid matrix, tween 80 with various concentrations as a stabilizer, and PEG 400 as co-surfactant. Characterization was conducted by determining the encapsulation efficiency (%EE), size measurement, particle size distribution, and zeta potential of SLN glibenclamide. SLN formation was also tested for its physical stability based on the heating-cooling cycle method. The optimum formula was obtained at the concentration of tween-80 of 1 mg/mL yielding the %EE value of 60.6194%, and pH 6.01. The results of particles diameter analysis were 175.5 ± 10.07 nm with a polydispersity index (PDI) of 0.1270, and zeta potential of +5.9 mV respectively. Stability testing by the heating-cooling cycle method has shown the instability of the SLN glibenclamide form under extreme temperatures and mechanics. It could be concluded that the results of characterization of glibenclamide SLN showed appropriate physical properties for nanoparticulate formulation.